Interspecific competition influences fitness benefits of assortative mating for territorial aggression in eastern bluebirds (Sialia sialis). - Morgan R Harris (Public Library of Science (PLoS), 2014)
Territorial aggression influences fitness and, in monogamous pairs, the behavior of both individuals could impact reproductive success. Moreover, territorial aggression is particularly important in the context of interspecific competition. Tree swallows and eastern bluebirds are highly aggressive, secondary cavity-nesting birds that compete for limited nesting sites. We studied eastern bluebirds at a field site in the southern Appalachian Mountains that has been recently colonized (<40 yr) by tree swallows undergoing a natural range expansion. The field site is composed of distinct areas where bluebirds compete regularly with tree swallows and areas where there is little interaction between the two species. Once birds had settled, we measured how interspecific competition affects the relationship between assortative mating (paired individuals that behave similarly) and reproductive success in eastern bluebirds. We found a strong tendency toward assortative mating throughout the field site. In areas of high interspecific competition, pairs that behaved the most similarly and displayed either extremely aggressive or extremely non-aggressive phenotypes experienced higher reproductive success. Our data suggest that interspecific competition with tree swallows may select for bluebirds that express similar behavior to that of their mate. Furthermore, animal personality may be an important factor influencing the outcome of interactions between native and aggressive, invasive species.